(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
Background. The impostor phenomenon (IP) — the persistent belief that one’s achievements are undeserved, accompanied by a fear of being “exposed” as a fraud — has been increasingly linked to social media environments that amplify upward social comparison and dependence on external validation. This study examined social-media-related negative self-evaluation, global self-esteem, and depressive symptoms through the theoretical lens of the impostor phenomenon among Uzbek youth. Methods. A secondary analysis was conducted on data from 1,605 respondents aged 17–35 years who completed an 18-item Uzbek-language questionnaire measuring the negative impact of social media on self-esteem (with three subscales: body image and emotional impact, social comparison and low self-worth, and dependence on external validation), the Rosenberg Self-Esteem Scale (RSES), the Beck Depression Inventory-II (BDI-II), and Raven’s Progressive Matrices. Correlational analyses, group comparisons, and an exploratory mediation analysis were performed. An integrative model of the impostor phenomenon guided interpretation. Results. Negative self-evaluation from social media correlated strongly and negatively with self-esteem (r = −.595, p < .001) and positively with depressive symptoms (r = .404, p < .001), but negligibly with intelligence (r = .034, ns). The impostor-relevant subscales — dependence on external validation and social comparison/low self-worth — showed the expected moderate associations with low self-esteem (r = −.452 and −.448) and depression (r = .306 and .327). Group differences by sex, age, and daily usage duration were small or nonsignificant (all η² ≤ .004), indicating that the experience is broadly distributed and not primarily a function of time online.